Media-influenced self-medication in Brazil (Research, Society and Development, 2022)
The objective is to estimate, through references and scientific articles, the impacts caused by the media and drug advertisements, as well as these factors increase the practice of self-medication, identifying the health risks that it can cause in the population. The present study is an integrative literature review, based on a bibliographic study, which aims to achieve a deep understanding of a given phenomenon based on previous studies. The pharmacist plays an important role in providing a measurement to prevent the irrational use of drugs, being a specialist who intends to provide medical care, in accordance with the law and code of conduct, guarantee services, i access to medicines, specialized administrative care and awareness of the dangers of adverse reactions, drug interactions and drug addiction. In this sense, the pharmacist is considered a health promoter and must provide information to the user who will choose the best product for the prevention and treatment of diseases, especially when the patient chooses to practice self-medication. The pharmacist is also responsible for identifying signs and symptoms of health problems and making decisions, advising the patient's referral to a doctor. The population is heavily influenced by drug advertisements, which indiscriminately produce self-medication. It is noticed in the studies the difficulty of medical professionals daily in the exercise of the role of directing the effective use of medicines, the practice of self-medication has always been used for a long time, mainly due to the difficulty of accessing the population in the health system. Advertising is intended to highlight the product also as a result of increasing its sales, leaving aside, in many cases, sometimes information about the safety of the drug, such as side effects, adverse reactions and drug interactions, showing only its benefits. and indicators.